Two-photon resonant excitation of interatomic coulombic decay in neon dimers. (16th September 2015) - Dubrouil, A; Reduzzi, M; Devetta, M; Feng, C; Hummert, J; Finetti, P; Plekan, O; Grazioli, C; Fraia, M Di; Lyamayev, V; Forge, A La; Katzy, R; et al.
Abstract: The recent availability of intense and ultrashort extreme ultraviolet sources opens up the possibility of investigating ultrafast electronic relaxation processes in matter in an unprecedented regime. In this work we report on the observation of two-photon excitation of interatomic Coulombic decay (ICD) in neon dimers using the tunable intense pulses delivered by the free electron laser FERMI. The unique characteristics of FERMI (narrow bandwidth, spectral stability, and tunability) allow one to resonantly excite specific ionization pathways and to observe a clear signature of the ICD mechanism in the ratio of the ion yield created by Coulomb explosion. The present experimental results are explained by ab initio electronic structure and nuclear dynamics calculations.